Assistance Task of the Indonesian National Army to the Police of the Republic of Indonesia (A Study of Legal Politics) - Hasan, Mohammad; Faisal, Faisal; Syahbandir, Mahdi; Gaussyah, M; Fikarda, Andini (SCAD Independent, 2025)
According to Law No. 34 of 2004 Article 8, one of the responsibilities of the Indonesian National Armed Forces is to perform the defense-related functions of the land-based Indonesian National Army. Empowering the land-based defensive zone is one of the other jobs. This indicates that the Indonesian National Armed Forces are also tasked with maintaining public security within the context of ensuring the safety of all citizens in the context of Military Operations for War (OMP) and Military Operations Other Than War (OMSP) on land. Therefore, it makes sense that the Indonesian National Armed Forces and the Police, who serve as the main pillars of the country's defense and security, collaborate to carry out their respective missions. The engagement of the Indonesian National Armed Forces in supporting the Police is hampered by several circumstances. One of them is the difficulty in implementing the support duty into their work patterns because there are now no laws or regulations controlling it. Even yet, it is crucial to understand how the participation mechanism works, how far the limits of involvement are pushed, and the circumstances in which the police must request aid from the Indonesian National Armed Forces for their tasks. This paper tries to examine the legal politics of the Indonesian National Armed Forces' objective in Aceh job of providing aid to the police.